THE SOLUTION OF THE EQUATIONS APPLYING THE GENERAL SERIES OF FIBONACCI - Tolbatov, Yevgeniy (Proceedings of National Aviation University (archive), 2014)
The effective method of solving equations using Fibonacci general series has been shown. The concept ofthe Fibonacci general series has been applied; the recurrence formula of the population volume change has beenobtained. We get the equation based on the recurrence formulas; the largest of this equation is the index of thepopulation volume change. There are some examples of the linear solving equations by means usage the Fibonaccigeneral series in the frame of Excel.